A search for triple Higgs boson production in the 6b final state using pp collisions at s√=13 TeV with the ATLAS detector - Aad, J; Abbott, B; Abeling, K; Chen, M; Frost, J; Huffman, B; Pacey, H (American Physical Society, 2025)
A search for the production of three Higgs bosons (HHH) in the bb¯bb¯bb¯ final state is presented. The search uses 126 fb−1 of proton-proton collision data at s√=13 TeV collected with the ATLAS detector at the Large Hadron Collider. The analysis targets both non-resonant and resonant production of HHH. The resonant interpretations primarily consider a cascade decay topology of X→SH→HHH with masses of the new scalars X and S up to 1.5 TeV and 1 TeV, respectively. In addition to scenarios where S is off-shell, the non-resonant interpretation includes a search for standard model (SM) HHH production, with limits on the tri-linear and quartic Higgs self-coupling set. No evidence for HHH production is observed. An upper limit of 59 fb is set, at 95% confidence level, on the cross-section for Standard-Model HHH production.